2006
DOI: 10.1002/humu.20280
|View full text |Cite
|
Sign up to set email alerts
|

Systematic mRNA analysis for the effect ofMLH1 andMSH2 missense and silent mutations on aberrant splicing

Abstract: A substantial proportion of MLH1 and MSH2 gene mutations in hereditary nonpolyposis colon cancer syndrome (HNPCC) families are characterized by nucleotide substitutions, either within the coding sequence (missense or silent mutations) or in introns. The question of whether these mutations affect the normal function of encoding mismatch DNA repair proteins and thus lead to the predisposition to cancer is determinant in genetic testing. Recent studies have suggested that some nucleotide substitutions can induce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
60
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 35 publications
8
60
1
Order By: Relevance
“…However, a combination of analyses seems to be more reliable than a single-software test, even if an analysis performed using different web tools is complicated by prediction discordance, particularly for ESE/exon splicing silencer creation or elimination, due to different algorithms used to evaluate nucleotide variations. A study conducted on ESEfinder and then confirmed on RescueESE8, 40,41 demonstrated that the prediction does not always correlate with an in vitro effect. Protein-prediction software tools are more reliable and there is greater agreement in their output data.…”
Section: Discussionmentioning
confidence: 99%
“…However, a combination of analyses seems to be more reliable than a single-software test, even if an analysis performed using different web tools is complicated by prediction discordance, particularly for ESE/exon splicing silencer creation or elimination, due to different algorithms used to evaluate nucleotide variations. A study conducted on ESEfinder and then confirmed on RescueESE8, 40,41 demonstrated that the prediction does not always correlate with an in vitro effect. Protein-prediction software tools are more reliable and there is greater agreement in their output data.…”
Section: Discussionmentioning
confidence: 99%
“…The single case (DSALLG15_R1) with MSH6 mutation (p. T915A) and no increase in the mutational burden carried an amino acid alteration predicted as benign by PolyPhen2 (31). Interestingly, the two cases with MLH1 mutation presented an identical alteration, a splicing mutation (X264_splice; rs267607789) observed in patients with Lynch syndrome (32). In addition, the second relapse of patient DSALLG11 displayed an exceptionally high number of SNVs (1225), possibly because of a synergistic effect of mutations both in MSH6 and SETD2 (33).…”
Section: Temporal Association Of Somatic Mutations Between Diagnosis Andmentioning
confidence: 94%
“…Splicing defects resulting from exonic substitutions have been found in a growing number of disease genes, such as CFTR [Pagani et al, 2005;Raponi et al, 2007], MLH1 [Auclair et al, 2006;Stella et al, 2001;Tournier et al, 2008], ATM [Teraoka et al, 1999], NF1 [Ars et al, 2000], SMN2 [Lorson and Androphy, 2000] or BRCA1 . The latter gene is one of the two most important breast cancer susceptibility genes [King et al, 2003], encoding a 1863 amino-acid protein involved in DNA damage repair and transcription regulation [Gowen et al, 1998].…”
Section: Introductionmentioning
confidence: 99%